Colistin Resistance Gene mcr-1 Mediates Cell Permeability and Resistance to Hydrophobic Antibiotics - Li, Baiyuan; Yin, Fang; Zhao, Xuanyu; Guo, Yunxue; Wang, Weiquan; Wang, Pengxia; Zhu, Honghui; Yin, Yeshi; Wang, Xiaoxue (Frontiers in Microbiology, 2020)
Colistin is considered the last-resort antibiotic used to treat multidrug resistant bacteria-related infections. However, the discovery of the plasmid-mediated colistin resistance gene, mcr-1, threatens the clinical utility of colistin antibiotics. In this study, the physiological function of MCR-1, which encodes an LPS-modifying enzyme, was investigated in E. coli K-12. Specifically, the impact of mcr-1 on membrane permeability and antibiotic resistance of E. coli was assessed by constructing an mcr-1 deletion mutant and by a complementation study. The removal of the mcr-1 gene from plasmid pHNSHP45 not only led to reduced resistance to colistin but also resulted in a significant change in the membrane permeability of E. coli. Unexpectedly, the removal of the mcr-1 gene increased cell viability under high osmotic stress conditions (e.g., 7.0% NaCl) and led to increased resistance to hydrophobic antibiotics. Increased expression of mcr-1 also resulted in decreased growth rate and changed the cellular morphology of E. coli. Collectively, our results revealed that the spread of mcr-1-carrying plasmids alters other physiological functions in addition to conferring colistin resistance.